Decolonizing the decolonization movement in global health: A perspective from global surgery - Bua, Emmanuel; Sahi, Saad Liaqat (Frontiers in Education, 2022)
There has been a recent increase in dialogues around decolonization in global health. We present a perspective from global surgery emphasizing personal experiences around equity in barriers to education and surgical missions, citing specific personal challenges and local perceptions that we have experienced as well as potential solutions. We also cite fundamental challenges to the movement to decolonize global surgery, including donor-directed priorities and the creation of partnerships based in genuine bilateral exchange. We cite several models of current programs aiming to address some of these challenges.